Electrochemical methods to characterize nanomaterial-based transducers for the development of noninvasive glucose sensors - Ismail, Nur Alya Batrisya; Abd-Wahab, Firdaus; Bader, Mamoun M.; Wan Salim, Wan Wardatul Amani (Springer International Publishing AG, 2018)
Electrochemical biosensors consist of electrodes modified with nanomaterials that contain immobilized biomolecules for analyte recognition and utilize electrochemical transduction; a glucose meter is an example of such a biosensor. Innovation in glucose monitoring includes non-invasive sensing, where alternative body fluids such as saliva can be used in place of blood, eliminating finger-pricking. However, the concentration of glucose in saliva is twofold lower than in blood, demanding a more sensitive transducer. For a decade, research focused on enhancing the transduction layer by modifying electrodes with nanomaterials that can increase electron transfer, enabling detection of glucose at much lower concentrations. The contribution of these nanomaterials towards enhancement of electron transfer can be understood via electrochemical characterization techniques such as cyclic voltammetry (CV), linear sweep voltammetry (LSV), and electrical impedance spectroscopy (EIS). This chapter provides the basis of the voltammetry techniques and EIS with example graphs from our current research. The aforementioned techniques were performed on screen-printed glassy carbon electrodes modified with reduced graphene–conductive polymer composites, with voltammetry measurements providing CV and LSV and EIS measurements, with EIS resulting in Bode and Nyquist plots and Randles equivalent circuit. Results from our study show a reversible electrode reaction that is diffusion controlled.